2020
DOI: 10.1021/acs.jpcb.0c00029
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Adamantylated Peptidoglycan Immunomodulators in Lipid Nanocarriers: NMR Shows That Cargo Fragments Are Available on the Surface

Abstract: We present an in-depth investigation of the membrane interactions of peptidoglycan (PGN)-based immune adjuvants designed for lipid-based delivery systems using NMR spectroscopy. The derivatives contain a cargo peptidoglycan (PGN) dipeptide fragment and an adamantyl group, which serves as an anchor to the lipid bilayer. Furthermore, derivatives with a mannose group that can actively target cell surface receptors on immune cells are also studied. We showed that the targeting mannose group and the cargo PGN fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…For example, addition of lipophilic adamantane groups to peptidoglycan fragments was shown to assist in the anchoring of these derivatives into the liposomal lipid bilayer, using NMR spectroscopy. 119 Likewise, straight-chain lipophilic anchors can be used for the same purpose, due to the extensive network of van der Waals interactions that they can form in the lipophilic bilayer of liposomes. Surprisingly, a reduction in chain length from C 18 to C 16 was shown to significantly increase the propensity for the undesired escape of lipids from liposomal membranes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, addition of lipophilic adamantane groups to peptidoglycan fragments was shown to assist in the anchoring of these derivatives into the liposomal lipid bilayer, using NMR spectroscopy. 119 Likewise, straight-chain lipophilic anchors can be used for the same purpose, due to the extensive network of van der Waals interactions that they can form in the lipophilic bilayer of liposomes. Surprisingly, a reduction in chain length from C 18 to C 16 was shown to significantly increase the propensity for the undesired escape of lipids from liposomal membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, within this study, we have explored the modification of the D-Glu at the α-COOH group. In addition to better ligand binding to NOD2, the proposed design will also enable greater exposure of the adamantane structure for possible membrane anchoring, compared to those of ManAdDMP analogs [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The more pronounced enhancement of pro-inflammatory cytokine and chemokine expression by l-AdTp compared to Man-l-AdTp could be explained by the negative influence of the hydrophilic mannose group on the incorporation efficiency into phospholipid vesicles. NMR studies of the PGN derivatives in model lipid assemblies have indeed confirmed that the non-mannosylated compounds have larger lipid incorporation efficiencies and penetrate the bilayer deeper than compounds with mannose groups [25].…”
Section: Discussionmentioning
confidence: 90%
“…Previous research on similar model PGN compounds with adamantyl-2-yl attachment incorporated into liposomes using atomic force microscopy revealed that the adamantane group is anchored into the lipid bilayer and that mannose residues are distributed at the surface of nanoparticles [26]. The localization and orientation of previously described adamantylated PGN derivatives in model lipid assemblies were also explored in detail using NMR spectroscopy, which showed the localization of bulky adamantane group in the interior of the bilayer and that of the D-iGln containing PGN fragment, as well as the presence of the mannose group on the surface of the bilayer [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation